Environmentally-friendly food processing - Mattsson, Berit, 1943-; Sonesson, Ulf.; ScienceDirect eBooks (Boca Raton : CRC Press ; Cambridge : Woodhead, 2003)
Environmental awareness in the food industry has become increasingly important in recent years, as a result of consumer pressure and increasing regulation. This book addresses how to achieve environmentally-friendly food production, reviewing the assessment of various food products and the ways in which the industry can improve their operations and become more environmentally responsible. Part one evaluates the environmental impact of food processing operations, in such areas as fruit, vegetable, meat and fish processing. Part two moves on to address good practice in food processing reviewing packaging, recycling and waste treatment, as well as methods of improving energy consumption and environmental training for the food industry. Environmentally-friendly food processing is an essential reference for all those concerned with environmental awareness and responsibility in the food industry. Addresses how to achieve environmentally-friendly food production, reviewing the assessment of various food products and how the industry can become more environmentally responsibleEvaluates the environmental impact of food processing operations, in such areas as fruit, vegetable, meat and fish processingReviews packaging, recycling and waste treatment, as well as methods of improving energy consumption and environmental training for the food industry.
8.5 Case study: pig slaughterhouse8.6 Future trends; 8.7 Sources of further information and advice; Chapter 9. The environmental management of packaging: an overview; 9.1 Introduction; 9.2 Packaging and the environment; 9.3 The regulatory context; 9.4 Packaging minimization; 9.5 Packaging recycling; 9.6 Future trends; 9.7 Sources of further information and advice; 9.8 References; 9.9 Acknowledgement; Chapter 10. Recycling of packaging materials; 10.1 Introduction; 10.2 Regulation in the EU; 10.3 Recycling paper packaging: collection and separation; 10.4 Recycling paper packaging: processing.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Food industry and trade -- Environmental aspects; TECHNOLOGY & ENGINEERING -- Food Science; Food industry and trade -- Environmental aspects; Food industry and trade -- Environmental aspects; Electronic books